PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL DENGAN PENDEKATAN SAINTIFIK BERBASIS ANDROID DI MADRASAH IBTIDAIYAH - Novita Purwa Hadi, M.Pd. (Madaris: Jurnal Guru Inovatif, 2021)
Development of Audio Visual Learning Media with scientific approach based Android in Madrasah Ibtidaiyah in order to meet the challenges and opportunities in Era 4.0. This research type is development research by using ADDIE model, namely: Analysis, Design, Development, Implementation, and Evaluation. The product is implemented to students Fifth grade students in MI Al Hidayah Domas Trowulan Mojokerto which are divided into 2 stages. Furthermore, it can be seen that the average percentage of results of the validation of material experts and media experts are 92% and 93%, it shows that the media are very feasible and do not require revision. The average percentage of students' attractiveness test results on learning media is 96%. Audio visual learning media with a scientific approach attracts students in receiving information on the teaching and learning process.